Let f(x)=x^2 and g(x)=x-3. Evaluate each expression. 1. `(f _og)(-2)` and `(g_og)(7)`  

2 Answers | Add Yours

jeew-m's profile pic

jeew-m | College Teacher | (Level 1) Educator Emeritus

Posted on

This is about composition of function.

In `(f_0g)(x)` we have to replace x in f(x) terms of x in g(x).

`f(x) = x^2`

`g(x) = x-3`

 

`(f_0g)(x) = (x-3)^2`

`(g_0g)(x) = (x-3-3) = (x-6)`

 

Then we can write the answers as;

`(f_0g)(-2) = (-2-3)^2 = 25`

`(g_0g)(7) = (7-6) = 1`

Sources:

Top Answer

oldnick's profile pic

oldnick | (Level 1) Valedictorian

Posted on

`f[g(x)]=(x-3)^2`          `f[g(-2)]=(-2-3)^2=25`

 

`g[g(x)]=(x-3)-3=x-6`       `g[g(7)]=7-6=1`

We’ve answered 315,699 questions. We can answer yours, too.

Ask a question